2004
DOI: 10.1002/ar.a.20093
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of immune cells: Evidence for neuroimmunomodulation in the liver

Abstract: Recent studies have demonstrated a pronounced influence by the autonomic nervous system on immune-mediated experimental hepatitis in the mouse. Adrenergic sympathetic neurons alleviate while capsaicin-sensitive peptidergic primary afferent neurons aggravate liver injury. This was evidenced by recording morphological and functional parameters upon chemical sympathectomy and application of ␤-adrenergic agonists, and capsaicin depletion of afferents, neurokinin receptor antagonists, and application of exogenous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 51 publications
2
18
0
1
Order By: Relevance
“…This study identifies extracellular ATP as a hepatic mitogen with implications about the regulation of liver growth and repair. Sympathetic nerves using NA and ATP as cotransmitters alleviate immunemediated experimental hepatitis in the mouse; it is speculated that nerve-immune cell interactions may offer novel therapeutic strategies in immune and inflammatory liver diseases (Neuhuber and Tiegs, 2004).…”
Section: Gastroenterologymentioning
confidence: 99%
“…This study identifies extracellular ATP as a hepatic mitogen with implications about the regulation of liver growth and repair. Sympathetic nerves using NA and ATP as cotransmitters alleviate immunemediated experimental hepatitis in the mouse; it is speculated that nerve-immune cell interactions may offer novel therapeutic strategies in immune and inflammatory liver diseases (Neuhuber and Tiegs, 2004).…”
Section: Gastroenterologymentioning
confidence: 99%
“…2,3 We recently reported that liver inflammation is also modulated by the autonomic nervous system. 4,5 Sympathetic efferent as well as primary sensory neurons are key players in the regulation of peripheral inflammation and immune responses. 1 Primary sensory neurons innervating inner organs are composed mainly of the peptidergic subpopulation of B-type primary afferents giving rise to unmyelinated C and thin myelinated A␦ fibers.…”
mentioning
confidence: 99%
“…15 The bidirectional communication between the nervous and immune systems results from the expression of specific receptors for cytokines and other immune mediators on neurons, as well as for neurotransmitters and neuropeptides on immune cells. 5,14 Although the kidney is frequently affected by immune-mediated pathologies such as various forms of glomerulonephritis (GN) or lupus erythematodes, to our knowledge, neuroimmune interactions have never been studied in this organ. Renal innervation consists of sympathetic and primary sensory nerve fibers.…”
mentioning
confidence: 99%
“…An influence of sympathetic nerves in immunemediated experimental hepatitis has been demonstrated [188], and ATP released as a cotransmitter might be involved. P2X7 receptors regulate NKT cells in autoimmune hepatitis [144].…”
Section: Hepatitismentioning
confidence: 99%